Epidemiology of bone injuries in elite athletics: A prospective 9-year cohort study - Kelly, S.; Waring, A.; Stone, B.; Pollock, N. (Physical Therapy in Sport, 2024)
Objectives To describe bone injury patterns in elite track and field athletes. To investigate relationships between bone injury and athlete characteristics to inform future injury prevention strategies.